A dinâmica das políticas de saúde e de assistência social no Brasil : incrementalismo e pontuações na atenção governamental entre 1986 e 2003 - Brasil, Felipe Gonçalves (2017)
This thesis analyzes the process of policy agenda setting focused on changes in health and social assistance policies in Brazil between 1986 and 2003. By mapping and analyzing the attention of actors and institutions involved in this policy process, we try to demonstrate moments of both balance and incremental change, as well as moments of rapid and profound changes in the chosen sector policies. Known in the public policy literature as the policy dynamics analysis, this thesis is based on the theoretical and methodological precepts of the Baumgartner and Jones (1993, 2005) Punctuated Equilibrium Theory. To do so, six types of documents were selected to analyze policymakers' attention: the legislative production approved in the period, messages to the National Congress sent annually by the Presidency of the Republic, minutes of the Subcommittee on Health, Assistance and Environment of the National Constituent Assembly of 1987, the Federal Constitution of 1988 and the reports of the National Conferences of Health and of Social Assistance realized within the temporal period of this thesis. In all, 23.174 data reflecting the attention of these actors on health and social care policies have been mapped, treated and analyzed in relation to their frequency, diversity and concentration over time. The thesis identifies the existence of institutional and cognitive frictions that constitute a propitious environment for changes during the first decades of Brazilian re-democratization. It also displays that variations in the attention of the actors can highlight moments of inflection and changes in policies. Still in the more general aspect, it puts in evidence the relation of the political, economic and social context and political turnovers with changes in attention on policies, sometimes leading to changes in public policies. The analysis of sector health and social assistance policies shows that, despite thematic proximity, these policies operate in distinct subsystems and focus the attention of decision makers independently. When analyzing health and care policies individually, this thesis confirms the existence of incremental moments, adjustments and small changes, but also points to changes that are specific and of great impact in both sectors. Finally, the paper reaffirms the importance of applying the Punctuated Equilibrium Theory as a theoretical and methodological basis for the study of agenda setting, policy change and policy dynamics, with this, opens a promising research agenda in this field of knowledge.